Land Use Change from Non-urban to Urban Areas Problems, Challenges and Opportunities - González-Jaramillo, Víctor Hugo; Novelli, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is related to land-use change and non-urban and urban relationships at all spatiotemporal scales and also focuses on land-use planning and regulatory strategies for a sustainable future. Spatiotemporal dynamics, socioeconomic implication, water supply problems and deforestation land degradation (e.g., increase of imperviousness surfaces) produced by urban expansion and their resource requirements are of particular interest. The Guest Editors expect that this reprint will contribute to sustainable development in non-urban and urban areas.